The tropics and the East-Central European gaze; The natural world of Southeast Asia in Polish and Serbian travel writings - Ewertowski, Tomasz (Wacana, Journal of the Humanities of Indonesia, 2022)
The article analyses representations of the natural world in Indonesia and mainland Southeast Asia in a corpus of Polish and Serbian travel writings for the period between the opening of the Suez Canal (1869) and the outbreak of the First World War (1914). The research is based on travel writings by twenty Polish and Serbian authors, who visited Southeast Asia during the period 1869-1914. Scrutinizing a corpus of such narratives should contribute to the study of perceptions of Southeast Asia, especially among travellers from very diverse backgrounds. The theoretical and conceptual framework of the article draws on works by other scholars who have analysed travel writings, imaginative geography, representations of Southeast Asia, and tropicality. The study focuses on four areas: 1) images of the luxuriant tropics, 2) images of the perilous tropics, 3) exploitation of its natural resources, and 4) nature and identity.